Subspecies and Distribution. L.t.tolaiPallas,1778—InnerMongolia(=NeiMongol),andGansu(NCChina). L.t.buchariensisOgnev,1922—TajikistanandNEAfghanistan. L.t.cheybaniBaloutch,1978—SWIran(ZagrosMts). L.t.cinnamomeusShamel,1940—SWSichuan,andNYunnan(SCChina). L.t.filchneriMatschie,1908—Shaanxi(CChina). L.t.lehmanniSevertzov,1873—SKazakhstan,Turkmenistan,andextremeN&NEIran,EtoSSiberia,Mongolia,andXinjiang(NWChina). L. t. swinhoei Thomas, 1894 — from Heilongjiang, Jilin, Liaoning, Inner Mongolia S to Hebei, Beijing, Henan, Shaanxi, Shanxi, and Shandong (NE & E China). The Tolai Hare occurs in the steppes E of the Caspian Sea, S to NE & SW Iran, E through the Middle Asian republics to Afghanistan, and from Kazakhstan and S Siberia to Mongolia, S Russian Far East, NW, C & NE China; an isolated population lives in S Iraq and SW Iran. A single specimen in South Asia might extend the distribution of the Tolai Hare as far S as Jammu and Kashmir, N India. in Leporidae - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
Subspecies and Distribution. L.t.tolaiPallas,1778—InnerMongolia(=NeiMongol),andGansu(NCChina). L.t.buchariensisOgnev,1922—TajikistanandNEAfghanistan. L.t.cheybaniBaloutch,1978—SWIran(ZagrosMts). L.t.cinnamomeusShamel,1940—SWSichuan,andNYunnan(SCChina). L.t.filchneriMatschie,1908—Shaanxi(CChina). L.t.lehmanniSevertzov,1873—SKazakhstan,Turkmenistan,andextremeN&NEIran,EtoSSiberia,Mongolia,andXinjiang(NWChina). L. t. swinhoei Thomas, 1894 — from Heilongjiang, Jilin, Liaoning, Inner Mongolia S to Hebei, Beijing, Henan, Shaanxi, Shanxi, and Shandong (NE & E China). The Tolai Hare occurs in the steppes E of the Caspian Sea, S to NE & SW Iran, E through the Middle Asian republics to Afghanistan, and from Kazakhstan and S Siberia to Mongolia, S Russian Far East, NW, C & NE China; an isolated population lives in S Iraq and SW Iran. A single specimen in South Asia might extend the distribution of the Tolai Hare as far S as Jammu and Kashmir, N India. Published as part of Don E. Wilson, Thomas E. Lacher, Jr & Russell A. Mittermeier, 2016, Leporidae, pp. 107-148 in Handbook of the Mammals of the World – Volume 6 Lagomorphs and Rodents I, Barcelona :Lynx Edicions on page 133, DOI: 10.5281/zenodo.6625539